2015
DOI: 10.2105/ajph.2014.302262
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Awareness and Use of Calorie Information After Mandatory Menu Labeling in Restaurants in King County, Washington

Abstract: Significant increases in calorie information awareness and use following regulation support the population-wide value of this policy. However, improvements varied across race, income, and gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 29 publications
4
33
3
Order By: Relevance
“…Similar to previous studies, the findings showed that women were more likely than men to use menu labeling, 11,14,24 as were those with higher education 24,25 and higher income 14,24,25 than their counterparts. Women had 2.8 times higher odds for being frequent menu labeling users than men in our study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to previous studies, the findings showed that women were more likely than men to use menu labeling, 11,14,24 as were those with higher education 24,25 and higher income 14,24,25 than their counterparts. Women had 2.8 times higher odds for being frequent menu labeling users than men in our study.…”
Section: Discussionsupporting
confidence: 88%
“…16 In this study using the same dataset, we further specified that among the same population, 25.6% were frequent users and 31.6% were moderate users. The findings showed a somewhat higher prevalence of menu labeling use than previous studies in single jurisdictions 14,23 and multiple jusrisdictions. 11,15 A 2010 study among 1,083 customers from King County, Washington, showed that while 60% of customers reported seeing menu labeling, only about 25% reported using it.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…This suggests that factors related to SES may have less impact on adolescents’ ability to use these labels relative to other types of nutrition labels, whereas research on restaurant menu calorie labeling has found that higher-income and higher-educated individuals are more likely to use menu calorie labels to make purchasing decisions. 19,20 Future research could investigate whether SSB warning labels are categorically different from (and perhaps more universally understood than) other labels, or whether the hypothetical setting contributed to the uniqueness of the present results.…”
Section: Discussionmentioning
confidence: 90%